"If You're Hyper It Calms You Down"; Young People's Experiences of an Irish Equine Facilitated Program. Issue 2 (3rd April 2021) - Hood, Philippa; Wilson, Charlotte
ABSTRACT: Equine Facilitated Programs (EFPs) appear to improve wellbeing in young people, however, empirical research is in its infancy. This study examined the experiences of young people participating in an EFP, and explored the mechanisms of change. Eight Irish socio-economically disadvantaged, adolescent males (aged 12–14 years; M = 13.86), with social and emotional difficulties took part in 31 semi-structured interviews and two focus groups over an eight week EFP. Thematic analysis generated three themes: Initial Engagement; Engagement with the Program; and Personal Growth. Potential mechanisms of change included curiosity, reciprocity, having a goal, and mastery of skills. EFPs may therefore improve wellbeing in young people through mechanisms that encourage both initial and ongoing engagement, and that support personal growth.